2017
DOI: 10.4236/jss.2017.57016
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal Behaviour in Bangladesh: A Scoping Literature Review and a Proposed Public Health Prevention Model

Abstract: The objectives of this review are to explore through a scoping analysis of published literature, the prevalence of suicidal ideation, attempts and suicide, and the correlates and presumed causes of such behaviours in Bangladesh, in order to develop a model of public health research and prevention. This type of review aims to contextualise existing knowledge, set it within a practice and policy context, and make recommendations for health care service delivery and evaluation. The evidence indicates an unusual p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 44 publications
0
34
0
Order By: Relevance
“…Other few studies reported the rate as 39.6 per 100,000 populations per year (Table 2) (Feroz et al 2012;Qusar et al 2009;Wu et al 2012). Suicides were happening more in rural areas of Bangladesh, especially in Chuadanga, Jenaidah, Kustia, Meherpur, Jashore and Chandpur (Chowdhury et al 2018;Shahnaz et al 2017;Arafat 2017;Feroz et al 2012). The country needs further larger studies to identify the near actual rate of suicides.…”
Section: Suicide Ratementioning
confidence: 98%
See 3 more Smart Citations
“…Other few studies reported the rate as 39.6 per 100,000 populations per year (Table 2) (Feroz et al 2012;Qusar et al 2009;Wu et al 2012). Suicides were happening more in rural areas of Bangladesh, especially in Chuadanga, Jenaidah, Kustia, Meherpur, Jashore and Chandpur (Chowdhury et al 2018;Shahnaz et al 2017;Arafat 2017;Feroz et al 2012). The country needs further larger studies to identify the near actual rate of suicides.…”
Section: Suicide Ratementioning
confidence: 98%
“…Suicide is grossly under reported and under registered in countries such as Bangladesh (Khan 2002(Khan 2005World Health Organization 2014;Chowdhury et al 2018;Shahnaz et al 2017). Moreover, there is no suicidal database in the country to report suicide metrics to the global agencies and to contribute in the global suicide statistics (Shah et al 2017;Arafat 2017;Chowdhury et al 2018).…”
Section: Suicide Ratementioning
confidence: 99%
See 2 more Smart Citations
“…This lengthy schooling is also considered as a predictor for developing depression & anxiety (Mao et al2019). Alarmingly, many Bangladeshi medical students had recently committed suicide (Shah et al 2017;Shahnaz et al 2017;Yeasmin 2018). Previous studies in other countries have shown that stress, depression and anxiety among undergraduate students remain underdiagnosed in more than 50% of cases.…”
Section: Introductionmentioning
confidence: 99%